2015
DOI: 10.1016/j.bbrep.2015.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Tetracyclines downregulate the production of LPS-induced cytokines and chemokines in THP-1 cells via ERK, p38, and nuclear factor-κB signaling pathways

Abstract: Recent reports have shown that antibiotics such as macrolide, aminoglycoside, and tetracyclines have immunomodulatory effects in addition to essential antibiotic effects. These agents may have important effects on the regulation of cytokine and chemokine production. However, the precise mechanism is unknown. This time, we used Multi Plex to measure the production of cytokines and chemokines following tetracycline treatment of lipopolysaccharide (LPS)-induced THP-1 cells. The signaling pathways were investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 36 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…Activation of ERK was not observed, probably because of the prolonged stimulation, ERK being phosphorylated after 30-60 minutes in THP1 monocytes. 31 In accordance with other studies, we show here that G i s are involved in MAPK activation induced by LPS, demonstrated by the reduction in p38 and JNK phosphorylation after treatment of monocytes with GOT. 5 Moreover, Lipo/GOT significantly reduced the phosphorylation of p38 and JNK compared with free GOT.…”
Section: Discussionsupporting
confidence: 93%
“…Activation of ERK was not observed, probably because of the prolonged stimulation, ERK being phosphorylated after 30-60 minutes in THP1 monocytes. 31 In accordance with other studies, we show here that G i s are involved in MAPK activation induced by LPS, demonstrated by the reduction in p38 and JNK phosphorylation after treatment of monocytes with GOT. 5 Moreover, Lipo/GOT significantly reduced the phosphorylation of p38 and JNK compared with free GOT.…”
Section: Discussionsupporting
confidence: 93%
“…Similarly, tetracyclines down-regulate the production of LPS-induced chemokines, such as CXCL8, CCL3 and CCL4 in THP-1 cells via NFκB signalling pathways. 46 The antiviral drug acyclovir inhibits the migratory potential of breast cancer cells. 47 These data indicate that silvestrol possibly attenuates inflammation by a reduction of immune cell attraction to the lesion site.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of prion-infected mice with the tetracycline antibiotics (doxycycline, minocycline and tetracycline) around the onset of the clinical phase has been shown to extend survival times [ 197 ]. Tetracycline antibiotics can suppress cytokine synthesis [ 198 ] and this might have a beneficial effect on CNS prion disease by reducing systemic inflammation. However, these antibiotics have also been shown to block PrP C –PrP Sc conversion and neurotoxicity [ 199 ].…”
Section: Cns Prion Diseasementioning
confidence: 99%